Strategic cyberwarfare. - Lillethun, Erik; Sharma, Rishi (Economic Inquiry, 2026)
This paper develops a theoretical model of cyberwarfare between nations, focusing on the factors that determine the severity and outcomes of cyber conflicts. We introduce a two‐country model where nations invest in offensive or defensive cyber capabilities across networked systems. We show that resource expenditure intensifies when players' effective values are similar, which can help explain the rise of cyberwarfare. We explore the implications of network structures, showing how larger attack surfaces worsen outcomes for defenders. Additionally, we investigate the impact of private cyber defence provision, and find that centralized policies may either improve or exacerbate cyber conflict.